Reconstruction of Inmate Rehabilitation Regulations Based on Principles of Legal Justice - Fri Hartono; Desy Kartika Caronina Sitepu; Anis Mashdurohatun; Debiantho; Mohamed Abdel Samad Mehanna (Islamic Research Publiser, 2025)
This study examines the reconstruction of inmate rehabilitation regulations grounded in principles of legal justice to address normative inconsistencies and practical disparities in the implementation of correctional policies. The research aims to critically analyse the extent to which existing rehabilitation regulations reflect substantive, procedural, and distributive justice, and to formulate a justice-oriented regulatory framework for inmate rehabilitation. Employing a qualitative juridical-normative approach, this study analyses statutory instruments governing correctional institutions, judicial doctrines on justice, and relevant scholarly literature, complemented by conceptual and comparative legal analysis. The findings reveal that current inmate rehabilitation regulations tend to prioritise administrative compliance and institutional order, while inadequately accommodating principles of proportionality, equality before the law, and restorative justice. Such regulatory orientation often results in unequal access to rehabilitation programs and undermines the correctional system's reintegrative objectives. This study proposes a reconstructed regulatory model grounded in legal justice principles, emphasising rights-based rehabilitation, restorative mechanisms, and fair assessment criteria for inmates. The study contributes to the development of correctional law by offering a normative framework that integrates legal justice into rehabilitation regulations, thereby supporting a more humane, equitable, and effective correctional system aligned with contemporary justice paradigms.